Extraction of antioxidant compounds from red pitaya using soxhlet extraction method - Wan Nurul Zahida, Wan Abdul Jalil (2009)
The fruits of Hylocereus cacti, known as red pitaya, have recently drawn much attention of growers worldwide, not only because of their red-purple colour and economic value as food products, but also for their antioxidant compounds especially Vitamin C. Vitamin C is essential to a health diet as well as being a highly effective antioxidant that capable of slowing or preventing the oxidation of other molecules. Oxidation reactions can produce free radicals, which start chain reactions that can damage cells. In this research, Soxhlet extractor was used to extract the Vitamin C from red pitaya. Then the extracts obtained were evaporated using rotary evaporator to get concentrated oil. The oil produced was analyzed using High Performance Liquid Chromatograph and Ultraviolet-Visible Spectrophotometer. The effects of different drying temperature, solvent polarity and solid to solvent ratio on extraction yields were investigated. The drying temperatures used were 350C, 500C, 600C and 700C. The solvents used were methanol, ethanol, hexane and toluene. In term of solid to solvents ratio, it was set at 5g: 400mL, 10g: 400mL, 15g: 400mL and 20g: 400mL. It was found that drying temperature at 600C with methanol as solvent and 15: 400mL solid to solvent ratio give the highest yields of vitamin C which was 3.87 mg/L and 61.67% of antioxidant activity. Thus, it can be concluded as the most suitable operating parameter for extraction of Vitamin C from red pitaya using Soxhlet extraction method.